EFFECTS OF PROBLEM BASED LEARNING STRATEGIES AND LEARNING STYLES AGAINST LEARNING ACHIEVEMENT JURISPRUDENCE OF STUDENTS MTS YASPI LABUHAN DELI - Sri Mariani (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2019)
Abstract: The teacher has an important role in creating an effective, conducive and attractive learningatmosphere so that students can be enthusiastic in receiving learning. This will have a positive effecton student learning achievement.The purposes of this study are to find out: (1) Effect of the applicationof problem based learning strategies on student Jurisprudence learning achievement in usury material,(2) Effect of the application of expository learning strategies on student Jurisprudence learning achievementin usury material, (3) Effect of learning styles on student Jurisprudence learning achievement in usurymaterial, (4) Interaction between learning strategies and learning styles on student learning outcomeson usury material.This research is quantitative research. This study used a quasi-experimental methodwith a population of 280 students of class IX MTS Yaspi Labuhan Deli consisting of 7 paralel classes.Sampling uses cluster random sampling, which consists of the experimental class and the controlclass of 40 students respectively. Data collection instruments are a test and quesioner. The analysistechnique is a two way anava at a significance of á = 0.05 followed by scheffe test.The resultsshowed: (1) the application of the problem based learning strategy had a significant effect on studentJurisprudence learning achievement in usury material seen from the value of pretest = 581 andposttest = 948,(2) there was a less significant effect of the implementation of the strategy expostori onstudent Jurisprudence learning achievement,(3) student learning achievement with visual learningstyles ( X = 23,5) higher than student learning achievement with kinesthetic learning styles (= 22,75),auditorylearning styles (= 22,40) and and (4) there is an interaction between learning strategies and learningstyles on learning achievement with statistical calculations Fcount = 20,11 > Ftable = 3.97.Keywords: Problem Based Learning Strategy, Learning Style, Learning Achievement